Reflections on poverty elimination in China by 2020 - Dash, Satya Prakash (Cappadocia Journal of Area Studies, 2020)
Poverty is a very complicated phenomenon with many states finding difficulty to control the phenomenon alone, forget about its elimination. China is a major country and had high incidence of poverty, but now it has eliminated poverty ‘absolutely’. It implemented certain programs for the economic betterment of the people. In this perspective, China has taken the lead and declared elimination of ‘absolute’ poverty in 2020. The paper analyses the policies and programmes that has been adopted with a very technical stern method and political determination so as to achieve this objective. It discusses the corruption element in poverty elimination and the steps taken to curb it. The paper exemplifies some successes and concludes with the commitment of President Xi in furthering the economic growth of China, especially after the Covid pandemic.